2011
DOI: 10.1021/ac200861k
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry Evidence for Cisplatin As a Protein Cross-Linking Reagent

Abstract: Cisplatin is a potent anti-cancer drug, which functions by cross-linking adjacent DNA guanine residues. However within one day of injection, 65~98% of the platinum in the blood plasma is protein-bound. It is generally accepted that cisplatin binds to methionine and histidine residues, but what is often underappreciated is that platinum from cisplatin has a 2+ charge and can form up to four bonds. Thus, it has the potential to function as a cross-linker. In this report, the cross-linking ability of cisplatin is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 51 publications
4
59
0
1
Order By: Relevance
“…The isotopic patterns of the [CaM+4Pt+nPt(NH 3 ) 2 +H] 13+ (n=2~6) ions were compared with the theoretical isotopic patterns, which fit with mean absolute deviation within 1.5 ppm range (see the inserts of Figure 1b′ and Table S-1). As previously observed, cisplatin preferentially binds to Met sites of CaM with all four cisplatin ligands displaced in low molar ratios of cisplatin-CaM mixtures; 35 herein, the maintenance of ligands, such as NH 3 , indicates that cisplatin might also bind to His, Asp or Glu residues in CaM sequence when increasing the concentration of cisplain in the cisplatin-CaM mixture. In addition, all the modified peaks shift to higher m/z region, namely, lower charge states, which supports the assumption that cisplatin binds to the carboxyl groups of Asp or Glu residues because deprotonation of a carboxyl group is needed before it binds to platinum(II).…”
Section: Results and Disscussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The isotopic patterns of the [CaM+4Pt+nPt(NH 3 ) 2 +H] 13+ (n=2~6) ions were compared with the theoretical isotopic patterns, which fit with mean absolute deviation within 1.5 ppm range (see the inserts of Figure 1b′ and Table S-1). As previously observed, cisplatin preferentially binds to Met sites of CaM with all four cisplatin ligands displaced in low molar ratios of cisplatin-CaM mixtures; 35 herein, the maintenance of ligands, such as NH 3 , indicates that cisplatin might also bind to His, Asp or Glu residues in CaM sequence when increasing the concentration of cisplain in the cisplatin-CaM mixture. In addition, all the modified peaks shift to higher m/z region, namely, lower charge states, which supports the assumption that cisplatin binds to the carboxyl groups of Asp or Glu residues because deprotonation of a carboxyl group is needed before it binds to platinum(II).…”
Section: Results and Disscussionsupporting
confidence: 81%
“…To further localize the binding sites of platinum to CaM, CaM-cisplatin adducts at different molar ratios (1:1, 1:2, and 1:8) were trypsin-digested and analyzed by MS. In the 1:1 molar ratio sample of trypsin-digested CaM-cisplatin, in addition to the previously reported cross-linked species, 35 another platinum cross-linked species CaM(107-126)+Pt+CaM(142-148) as well as platinum modified CaM(38-74), CaM(107-126), and CaM(127-148) were also observed. The same Pt-modified peaks were also observed in the CaM-cisplatin (1:2) sample; however, when the molar concentration of cisplatin is eight times higher than CaM, the intensities of all Pt-modified peaks dropped significantly, and most of them could be barely detected (Figure S-2).…”
Section: Results and Disscussionsupporting
confidence: 59%
See 1 more Smart Citation
“…[78,79] A combination of different fragmentation techniques (CID and ECD) as well as ion mobility mass spectrometry (IM-MS) allowed the determination of the sulfur atom of the methionine residue of substance P as the favoured binding site of cisplatin, whereas the His residues of angiotensin II and bombesin appeared to be preferred. [78][79][80] Tandem mass spectrometry techniques have been used to characterize cisplatin interactions with were recorded and showed that, even though the interactions between the complexes and the DNA strands were non-covalent in nature, they were strong enough to be observed in the gas phase during the analysis, and confirmed that PPCs do significantly stabilise the duplex structure of the oligonucleotide strands.…”
Section: Platinum Complexesmentioning
confidence: 97%
“…1 and 2) has become the instrument of choice for proteomics, 3 biological imaging, [4][5][6] and other research involving complex mixtures 7 or macromolecules. [8][9][10] Positioned within an ultra high vacuum chamber (<10 −9 mbar), an ion cyclotron resonance (ICR) cell is the main analyzing component of FT-ICR MS. The ICR cell detects ion motion in the magnetic field by electrostatic induction.…”
Section: Introductionmentioning
confidence: 99%